2016
DOI: 10.1016/j.archger.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Quality in residential care from the perspective of people living with dementia: The importance of personhood

Abstract: Supporting personhood was identified as a critical key concept underpinning quality residential aged care, from the perspective of both people with cognitive impairment and their family members. This highlights the important contribution that the psychological and social characteristics of care make to providing a good quality residential care experience from the perspective of consumers with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
136
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(140 citation statements)
references
References 12 publications
3
136
0
1
Order By: Relevance
“…Enjoyment can be experienced during activity participation (Nyman & Szymczynska, ; Roland & Chappell, ), when looking forward to an activity (Roland & Chappell, ) or enjoyment of the outcome of an activity (Bishop & Purcell, ). Activities may be enjoyed for various reasons such as being a hobby (Bishop & Purcell, ), a means of relaxation (Bishop & Purcell, ; Han et al, ) or a connection to personal identity (Carless, ; Han et al, ; Milte et al, ). In a study examining “meaningful activity” in RACFs, people with dementia as well as care staff commonly identified enjoyment as a measure for whether an activity was meaningful (Harmer & Orrell, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enjoyment can be experienced during activity participation (Nyman & Szymczynska, ; Roland & Chappell, ), when looking forward to an activity (Roland & Chappell, ) or enjoyment of the outcome of an activity (Bishop & Purcell, ). Activities may be enjoyed for various reasons such as being a hobby (Bishop & Purcell, ), a means of relaxation (Bishop & Purcell, ; Han et al, ) or a connection to personal identity (Carless, ; Han et al, ; Milte et al, ). In a study examining “meaningful activity” in RACFs, people with dementia as well as care staff commonly identified enjoyment as a measure for whether an activity was meaningful (Harmer & Orrell, ).…”
Section: Resultsmentioning
confidence: 99%
“…Harmer and Orrell () suggest that pure engagement entails deep involvement in the activity, implying that engagement requires more than simply being physically present during an activity. In one study, family members of RACF residents with dementia suggested that for activities to be engaging they need to be at a level of difficulty that requires the individual to concentrate on what they are doing but without being unachievable (Milte et al, ). An example of an activity for RACF residents that is not typically considered meaningful is falling asleep in front of the television (Morley, Philpot, Gill, & Berg‐Weger, ).…”
Section: Resultsmentioning
confidence: 99%
“…Supporting personhood has been identified as a foundation for quality care for people living with dementia [40]. Person-centred care centres on relationships with others and the theory that warm and compassionate care interactions should increase well-being, while disrespectful and disengaged care interactions are thought to lead to decreased well-being and increased agitation [14].…”
Section: Resultsmentioning
confidence: 99%
“…For example, in Definition 1, the defining attributes of ‘dementia friendly’ are empowerment, aspiration, self-confidence, contribution, participation, and meaningful activities [8]. These attributes may imply that the purposes of becoming dementia friendly are to acknowledge the ‘personhood’ of PWD [12], and to sustain their sense of meaning in life. In Definition 2, the essential attributes of ‘dementia-friendly’ include way-finding ability, a sense of safety, accessibility to local facilities, social acceptance, and understanding of dementia [10].…”
Section: Communities Working Towards Becoming Dementia Friendlymentioning
confidence: 99%